EVALUATION OF WASTE OF VEGETABLES AND FRUITS IN A MEAL PRODUCTION UNIT - Leysse Lourenço Lacerda; Bárbara Cristina Alves Saraiva; Yolanda Lage Silva; Márcia Regina Pereira Monteiro (Universidade do Estado do Rio de Janeiro, 2014)
This study evaluated the waste of vegetables and fruits in pre-preparation in commercial and hospital Meal Production Units in the city of Belo Horizonte-MG. The samples were collected during three weeks in each unit by Nutrition students. Twenty kinds of vegetables and fruits (4 fruits and 16 vegetables) were chosen, weighed before and after cleaning and selection, process performed three times for each type of food. The waste in pre-preparation was assessed by calculating the correction factor. Data were tabulated in Microsoft Excel 2010® program and statistical analyses performed using the Statistical Package for Social Sciences version 17.0. It was found that among the foods analyzed, ten did not differ statistically, showing statistical relevance of these factors. The commercial production unit has lower correction factors or similar to literature, compared with hospital production. In general, the waste presented by some food types analyzed was mostly higher than determined by literature as acceptable. Thus, investments are necessary in personal training, equipment calibration, exchange of utensils, and selection of better suppliers. DOI: http://dx.doi.org/10.12957/demetra.2014.8522